PENERAPAN PROTOKOL KESEHATAN COVID-19 OLEH REMAJA DI KECAMATAN MENGWI KABUPATEN BADUNG TAHUN 2021 - Pratiwi, Ni Ketut Ita; Kardiwinata, Made Pasek (ARCHIVE OF COMMUNITY HEALTH; Vol 9 No 1 (2022): April 2022, 2022)
The implementation of the health protocol is one of the efforts to break the chain of transmission and reduce the COVID-19 death rate. The low level of implementation of health protocols can lead to violations and risk being vulnerable to COVID-19 transmission. Based on the results of a survey conducted in six regions in Indonesia, 41.30% of violations of the application of the protocol were dominated by teenagers. The purpose of this study was to determine the relationship between sociodemographic characteristics, knowledge and attitudes towards the implementation of the COVID-19 health protocol in Mengwi District, Badung Regency. Quantitative research design with a cross sectional approach on 149 respondents selected by probability sampling, namely multi-stage sampling. The results in this study indicate that most of the adolescents in Mengwi District have implemented health protocols which are categorized as good 75.17%. It was also found that the variables that had a significant relationship to the implementation of the COVID-19 health protocol were age, gender, knowledge and attitudes. While the variables that do not have a significant relationship to the implementation of the COVID-19 health protocol are the level of education, parents' income, and place of residence. The policy makers in Mengwi District are optimizing education, counseling and health promotion to improve the behavior of implementing health protocols as an effort to prevent COVID-19 in adolescents in Mengwi District. Keywords : Health Protocol, COVID-19, Adolescents , Mengwi